Heparin-Binding Protein (HBP): A Causative Marker and Potential Target for Heparin Treatment of Human Sepsis-Induced Acute Kidney Injury. Issue 3 (September 2017) - Fisher, Jane; Russell, James A.; Bentzer, Peter; Parsons, Devyn; Secchia, Stefano; Mörgelin, Matthias; Walley, Keith R.; Boyd, John H.; Linder, Adam
ABSTRACT: Rationale: Sepsis-induced acute kidney injury (AKI) is a common condition with high morbidity and mortality. Neutrophil-derived heparin-binding protein (HBP) induces vascular leakage and is a promising biomarker of sepsis-induced organ dysfunction. It remains unknown if HBP is prognostic of AKI in septic shock and if HBP could play a role in the pathophysiology of sepsis-induced AKI. Objectives: To determine the association of plasma HBP levels with development of AKI, investigate the role of HBP in the pathophysiology of sepsis-induced AKI, and test the effect of blocking HBP using heparin derivatives. Methods: In 296 septic shock patients from the randomized multicenter Vasopressin and Septic Shock Trial (VASST) plasma HBP levels were associated with development of AKI and need for renal replacement therapy (RRT). Human renal tubular cells were exposed to recombinant HBP to evaluate inflammation and heparin derivatives were used to abrogate these effects. Finally, mice were exposed to HBP with and without heparin derivatives and the kidneys examined for signs of inflammation. Findings: Plasma HBP levels were significantly higher in patients with AKI and those requiring RRT. HBP levels identified patients with moderate AKI with an area under curve (AUC) of 0.85. HBP increased IL-6 production in renal tubular epithelial cells. Different heparin derivatives abrogated the HBP-induced increased inflammatory response in vitro and in vivo . Conclusion: Elevated plasma HBP is associated with development of sepsis-induced AKI and HBP is involved in its pathophysiology. Our studies suggest that heparin(s) could be tested for efficacy and safety of prevention of sepsis-induced AKI. Abstract : Supplemental Digital Content is available in the text